Step-up DC-DC Boost Converter Control with PID Controller and Artificial Neural Network - Anis Issa; Murad Altaira; Gaber Agela (African Journal of Advanced Pure and Applied Sciences, 2024)
These days, energy markets are witnessing a shift to renewable and sustainable energy sources, which increases demand for power electronic devices, especially DC-DC boost converters. This letter examines the problem of the voltage of the output adjustment of a DC-DC boost converter connecting with a resistive load. This study introduces a comparison between two techniques, namely artificial neural network (ANN) and PID controller to adjust the voltage of the output of the DC-DC boost converter. The simulation outcomes display that the ANN control technique gives a better dynamic response than the PID controller.